2021
DOI: 10.53713/nhs.v1i2.51
|View full text |Cite
|
Sign up to set email alerts
|

Management Of Diabetes Mellitus Type 2 For Elderly: Taichi Exercise To Reduce Blood Sugar Levels

Abstract: Elderly are high risk for the development of type 2 diabetes due to the combined effects of increasing insulin resistance and impaired pancreatic function with aging. Diabetes mellitus is a chronic disease that causes insulin in the pancreas is not effective one of the treatments that can be done by diabetics to reduce blood sugar levels One of them with physical activity, the activity is taichi exercises.The purpose of this study was to investigate the effect of taichi exercises on reducing blood sugar levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…It finally achieves therapeutic effects on the body and mind (39). Other studies have shown that taijiquan practice can also improve the practitioner's stress function (40,41) and promote the body to secrete norepinephrine and dopamine substances (6,42). These substances will help the body to generate exercise drive, so that the central nervous system in the body achieves a relative balance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It finally achieves therapeutic effects on the body and mind (39). Other studies have shown that taijiquan practice can also improve the practitioner's stress function (40,41) and promote the body to secrete norepinephrine and dopamine substances (6,42). These substances will help the body to generate exercise drive, so that the central nervous system in the body achieves a relative balance.…”
Section: Discussionmentioning
confidence: 97%
“…Scholars such as Raglin (3), Chekroud et al (4), and De Sousa et al (5) believe that regular physical activity can reduce depression, anxiety, and reduce the risk of suffering from mental illness. Among them, taijiquan therapy is gradually accepted internationally and will be included in the list of World Intangible Cultural Heritage in 2020 (6). It takes taijiquan and yin-yang dialectical thinking of Confucianism and Taoist philosophy in traditional culture as the core concept.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension must be handled properly in the elderly to prevent the risk of morbidity and mortality during the COVID-19 period. There are two treatments, namely pharmacological and non-pharmacological, namely by relaxation techniques (Pati et al, 2014;Kurdi et al, 2021). Relaxation therapy is needed in hypertensive patients to make blood vessels relax (Savitri & Ratnawati, 2022), causing vasodilation causes blood pressure to return to normal (Kurdi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There are two treatments, namely pharmacological and non-pharmacological, namely by relaxation techniques (Pati et al, 2014;Kurdi et al, 2021). Relaxation therapy is needed in hypertensive patients to make blood vessels relax (Savitri & Ratnawati, 2022), causing vasodilation causes blood pressure to return to normal (Kurdi et al, 2021). To make a body being relaxed can be done in several ways such as music therapy classical, yoga, deep breathing techniques, and massage therapy (Muttaqin, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tai chi is one of the modalities to improve the quality of life of the elderly. In this tai chi exercise, it is more important to balance and synchronize breathing and movement (Kurdi, Abidin, Priyanti, & Kholis, 2021). In addition, this exercise consists of movements in the hands and feet that are carried out simultaneously, slowly, with a soft rhythm and integrated with breathing to improve balance and reduce the risk of falling in the elderly (Zhou, Zhao, Fan, Li, & Chen, 2021).…”
Section: Introductionmentioning
confidence: 99%